Effect of Sodium Hypochlorite and Benzalkonium Chloride on the Structural Parameters of the Biofilms Formed by Ten Salmonella enterica Serotypes - Capita, Rosa (Pathogens, 2019)
The influence of the strain on the ability of Salmonella enterica to form biofilms on polystyrene was investigated by confocal laser scanning microscopy. The effects of sodium hypochlorite with 10% active chlorine (SHY; 25,000, 50,000, or 100,000 ppm), and benzalkonium chloride (BZK; 1000, 5000, or 10,000 ppm) on twenty-four-hour-old biofilms was also determined. The biofilms of ten Salmonella enterica isolates from poultry (S. Agona, S. Anatum, S. Enteritidis, S. Hadar, S. Infantis, S. Kentucky, S. Thompson, S. Typhimurium, monophasic variant of S. Typhimurium 1,4,(5),12:i:-, and S. Virchow) were studied. Biofilms produced by S. Anatum, S. Hadar, S. Kentucky, and S. Typhimurium showed a trend to have the largest biovolume and the greatest surface coverage and thickness. The smallest biofilms (P < 0.01) in the observation field (14.2 × 10(3) µm(2)) were produced by S. Enteritidis and S. 1,4,(5),12:i:- (average 12.9 × 10(3) ± 9.3 × 10(3) µm(3)) compared to the rest of the serotypes (44.4 × 10(3) ± 24.7 × 10(3) µm(3)). Biovolume and surface coverage decreased after exposure for ten minutes to SHY at 50,000 or 100,000 ppm and to BZK at 5000 or 10,000 ppm. However, the lowest concentrations of disinfectants increased biovolume and surface coverage in biofilms of several strains (markedly so in the case of BZK). The results from this study suggest that the use of biocides at low concentrations could represent a public health risk. Further research studies under practical field conditions should be appropriate to confirm these findings.